Long-term value creation of private equity firms with evidence from the Nordic countries - Branding, Alexander (2018)
This paper aims to study the long-term value creation of Private Equity firms by comparing their after performance utilizing the post IPO performance of PE-backed vis-à-vis non-backed IPOs in the Nordic countries (Sweden, Norway, Denmark, Finland and Iceland), from 2001 to 2016. Moreover, this paper aims to analyse whether certain PE-related firm characteristics drive stock performance and if there is any sizable difference relative to non-backed firms.